Professional Competence Of Integrated Islamic School Teachers: Systematic Literature Review And Meta-Analysis - Tarihoran, Naf'an; Nugraha, Enung; Supianto, Supianto (Peneliti.net, 2025)
Professional competence of teachers in Integrated Islamic Schools (SIT) represents a complex phenomenon that requires a comprehensive understanding due to its unique characteristics of integrating Islamic values with national educational standards. According to the Indonesian Ministry of National Education Regulation No. 16 of 2007, professional competence encompasses mastery of materials, structures, concepts, and scientific thinking patterns that support the subjects taught, which becomes more complex in the SIT context due to dual curriculum requirements. This study aims to conduct a systematic literature review and meta-analysis to analyze the characteristics, influencing factors, and impacts of professional competence among SIT teachers. The research employed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, searching three major databases (ERIC, ScienceDirect, and PubMed) with a total of 43.985 initial articles. These articles were systematically filtered to yield 7 articles that met the inclusion criteria for meta-analysis. The meta-analysis revealed a moderate to large effect size of 0.60 (95% CI: 0.52-0.68, p<0.001), indicating that professional competence significantly influences various educational outcomes in SIT, with the strongest correlation (r=0.68) found between professional competence and teacher work productivity, contributing 70.2% effectiveness. The study recommends developing a comprehensive and contextual professional competence framework for SIT teachers, designing continuous training programs that integrate pedagogical, technological, and spiritual dimensions, and strengthening supervision and evaluation systems based on Islamic values.